Primates : the fearless science of Jane Goodall, Dian Fossey, and Biruté Galdikas - Ottaviani, Jim (Square Fish, an imprint of Macmillan, 2015)
"Jim Ottaviani returns with an action-packed account of the three greatest primatologists of the last century: Jane Goodall, Dian Fossey, and Biruté Galdikas. These three ground-breaking researchers were all students of the great Louis Leakey, and each made profound contributions to primatology--and to our own understanding of ourselves." -- Amazon.com